NGHIÊN CỨU KHẢ NĂNG CHẾ TẠO MÀNG MỎNG CỦA MỘT SỐ CACBOXYLAT ĐẤT HIẾM BẰNG PHƯƠNG PHÁP LẮNG ĐỌNG HƠI HÓA HỌC - Nguyệt, Triệu Thị; Hiền Lan, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
Some thin films of rare earth oxides Nd2O3, Sm2O3 and Yb2O3 were prepared from Nd(Piv)3, Sm(Isb)3 and Yb(Piv)3 (Piv: pivalat, Isb: isobutyrat) using the chemical vapor deposition method (CVD). The crystal structures of thin films have been determined by X-ray diffraction. The surface structure and thickness of thin film have been determined by scanning electron microscopy (SEM). The obtained results show that the films deposited at 450oC are all single cubic structure and they seem to be uniform.